UPAYA GURU BAHASA ARAB DALAM MENGATASI PROBLEMATIKA MEMBACA TEKS BAHASA ARAB PADA SISWA MADRASAH IBTIDAIYAH - Alvina Dewi Anggraini; Ahmad Nur Mizan; Zulhannan; Intan Muflihah (Berajah Journal, 2026)
This study was motivated by the low ability of sixth-grade students at MI Miftahul Huda Punggur, Central Lampung, in reading Arabic texts, which is indicated by errors in makhraj pronunciation, inability to distinguish vowel marks, limited vocabulary mastery, and low learning motivation. This study aims to describe the learning process of reading Arabic texts, identify the students’ reading problems, and analyze the teacher’s efforts to overcome these problems. This research employed a qualitative approach with a case study design. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results showed that students’ reading ability was still varied with an average score of 64.8, where 54% of students achieved learning mastery and 46% did not. The reading problems were influenced by internal factors such as low motivation, lack of self-confidence, and limited vocabulary mastery, as well as external factors such as limited teaching methods and learning media. The teacher’s efforts to overcome these problems were carried out through drill methods, talaqqi, repeated reading exercises, the use of vocabulary flashcards, motivation and rewards, and additional tutoring outside class hours. These strategies were proven to improve reading fluency, pronunciation accuracy, and student participation in learning.